Emergent Web Intelligence : Advanced Semantic Technologies - Chbeir, Richard; Abraham, Ajith; Hassanien, Aboul Ella (London : Springer, 2010)
The future of the World Wide Web depends on its ability to understand and automatically process content to enable computers and people to work in cooperation. Now more than ever, new advanced techniques and intelligent approaches are required to transform the Web into a universal reasoning and semantic-driven computing machine. The Web intelligence discipline attempts to deal with this challenge by exploiting information technologies and artificial intelligence approaches to design the next generation of web-empowered systems and future Internet services.'The Emergent Web Intelligence: Advanced Semantic Technologies' book provides valuable references and cutting-edge technologies for anyone interested in exploring how semantic techniques and technologies can bridge the gap between users and applications on the Web. This book presents cutting-edge research in the field of semantic technologies. Its seventeen chapters are arranged into four parts and identify interdisciplinary challenges in the areas of the Semantic Web, artificial intelligence, and knowledge-based services. The chapters provide analysis and insight into semantic Web techniques and are authored by reputable scientists in the field. All articles are self-contained to provide the greatest reading flexibility and aim to serve as a reference for researchers in the Semantic Web community.
Gifted by Ajith Abraham
Includes bibliographical references and index
Keywords: Semantic Web -- Technologies; Expert systems (Computer science); Web Intelligence